2021
DOI: 10.3389/fpsyg.2021.756767
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Moderating Effect of Interpersonal Emotion Regulation Between the Integration of Opportunity and Resource and Entrepreneurial Performance

Abstract: This study explains how start-ups obtain a high accumulated performance by aligning and employing an integration between opportunities and resources (IOR) in a dynamic environment and whether these potential benefits are associated with interpersonal emotion regulation. Using 274 enterprise samples, the findings confirm that an IOR has a significant positive effect on entrepreneurial performance. In addition, positive emotion and interpersonal relationship regulation positively moderate the relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
(56 reference statements)
1
6
0
Order By: Relevance
“…The relationship between opportunities and resources is complex, but the research on them is fragmented. The introduction of the IORC helps to clarify the connection between opportunities and resources, and makes them form an “integration effect” in the process of entrepreneurship ( Li et al, 2021 ). Reviewing the existing research, Shane and Venkataraman (2000) argued that the essence of entrepreneurial behavior is opportunity identification and opportunity utilization Brown et al (2001) and Baker and Nelson (2005) , pointed out that resource development can solve the resource constraints in the early stage of entrepreneurship, and Ge et al (2016) outlined the connotation of “the opportunity in resource” and “the resource in opportunity” from a systematic perspective.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 3 more Smart Citations
“…The relationship between opportunities and resources is complex, but the research on them is fragmented. The introduction of the IORC helps to clarify the connection between opportunities and resources, and makes them form an “integration effect” in the process of entrepreneurship ( Li et al, 2021 ). Reviewing the existing research, Shane and Venkataraman (2000) argued that the essence of entrepreneurial behavior is opportunity identification and opportunity utilization Brown et al (2001) and Baker and Nelson (2005) , pointed out that resource development can solve the resource constraints in the early stage of entrepreneurship, and Ge et al (2016) outlined the connotation of “the opportunity in resource” and “the resource in opportunity” from a systematic perspective.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Reviewing the existing research, Shane and Venkataraman (2000) argued that the essence of entrepreneurial behavior is opportunity identification and opportunity utilization Brown et al (2001) and Baker and Nelson (2005) , pointed out that resource development can solve the resource constraints in the early stage of entrepreneurship, and Ge et al (2016) outlined the connotation of “the opportunity in resource” and “the resource in opportunity” from a systematic perspective. Based on this, this paper takes internal and external resources as the dividing line and divides the interaction between resources and opportunities into two parts ( Li et al, 2021 ): internal integration (ITI) and external integration (ETI), as shown in Figure 1 .…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, this paper reveals the boundary conditions of the underdog status affecting resource efficiency. Existing research has shown that integrating an opportunity and resource perspective can improve entrepreneurial performance in individuals with high levels of vocational interests, grit, and regulated emotions ( Arco-Tirado et al, 2019 ; Bergner, 2020 ; Li et al, 2021 ). This research shifts the benefit of a group of underdog entrepreneurs from internal psychological capital to external environmental-related factors.…”
Section: Introductionmentioning
confidence: 99%